SUSTAINABLE DEVELOPMENT IN URBAN INDUSTRIALIZATION ERA (CASE STUDY BONTANG CITY) - Budiman Budiman; Jumansyah Jumansyah; Zulkifli Abdullah; Andi Molang Chaerul (DIA: Jurnal Administrasi Publik, 2021)
Sustainable development has become the main indicator for all local governments to sharpening urban development management. By seeing the differences in economic, social, and environmental potential in urban areas in Indonesia, it has different opportunities and challenges to embody, thus this research aims to explore and discover concepts/patterns of sustainable development in Bontang City, East Kalimantan Province. The results of the study indicate that sustainable development has been constructed through collective collegial approaches, transparency, business, and direct involvement of the private sector and society to attain. So the concept not only improves community participation, but it has changed people's behavior were just as a consumer/an object before, then to be an actor.